On recoverability of finite traces of square-summable sequences - Dokuchaev, Nikolai
The paper investigates recoverability of infinite sequences (discrete time signals) from incomplete observations. It is shown that under very mild restrictions on the location of the observed and missed data, recoverability of finite traces of signals can be achieved for wide classes of signals that everywhere dense in the space of square-summable signals.